2015
DOI: 10.1002/oby.21158
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index trajectories from ages 1 to 20: Results from two nationally representative canadian longitudinal cohorts

Abstract: Objective: In this study, unique body mass index (BMI) trajectories from ages 1 to 20 years were identified; each trajectory according to socio demographic and family characteristics was described. Methods: Participants came from two national population surveys (n 5 7,253; n 5 901) and were aged 1-6 years at baseline. Children were surveyed biennially over eight waves up to 14-20 years of age. BMI trajectories by sex and survey cohort were identified by group-based trajectory modeling. After crossvalidating tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 33 publications
7
37
1
Order By: Relevance
“…Only a limited number of studies provided detailed insight into the developmental trajectories of BMI from early adolescence until young adulthood . Three studies using GMM found four distinct BMI trajectories, and one study identified two trajectory classes . In this last study, the identified trajectories were similar to the normal weight and the early onset overweight trajectories identified in the current study .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Only a limited number of studies provided detailed insight into the developmental trajectories of BMI from early adolescence until young adulthood . Three studies using GMM found four distinct BMI trajectories, and one study identified two trajectory classes . In this last study, the identified trajectories were similar to the normal weight and the early onset overweight trajectories identified in the current study .…”
Section: Discussionsupporting
confidence: 70%
“…In one of the other studies that constrained the variances across classes to be equal, four parallel trajectories were identified . The studies identifying four nonparallel trajectories had solutions resembling the findings of the current study .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Group‐based trajectory modeling enables the data themselves to divide a study population into subgroups that present distinct patterns and to fit its own trajectory models for each of those subgroups . Several studies have applied the group‐based trajectory approach to identify distinct weight gain patterns . However, few studies have examined the association between diverse weight gain trajectory patterns in the first 2 years of life and adiposity levels later in life.…”
Section: Introductionmentioning
confidence: 99%
“…The early programming hypothesis posits that a stimulus or insult experienced during a critical period of development causes permanent alterations in the development and organization of key tissues and organ systems that lead to irreversible changes in the structure and function of the body (10). Several studies have provided supportive data for the link between more rapid weight gain in infancy and an increased risk of developing obesity in later life (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, there are knowledge gaps that limit our insight regarding this link.…”
Section: Introductionmentioning
confidence: 99%